LncRNA CAI2 Contributes to Poor Prognosis of Glioma through the PI3K-Akt Signaling Pathway - Jiang, Yu; Zhang, Jinhui; Yu, Shengjin; Zheng, Linlin; Shen, Yue; Ju, Weiwei; Lin, Lijuan (Combinatorial Chemistry & High Throughput Screening, 2024)
Aims: We aim to explore new potential therapeutic targets and markers in human glioma. Background: Gliomas are the most common malignant primary tumor in the brain. Objective: In the present research, we evaluated the effect of CAI2, a long non-coding RNA, on the biological behaviors of glioma and explored the related molecular mechanism. Methods: The expression of CAI2 was analyzed using qRT-PCR in 65 cases of glioma patients. The cell proliferation was determined with MTT and colony formation assays, and the PI3K-AKt signaling pathway was analyzed using western blot. Results: CAI2 was upregulated in human glioma tissue compared with the matched, adjacent nontumor tissue and was correlated with WHO grade. Survival analyses proved that the overall survival of patients with high CAI2 expression was poor compared to that of patients with low CAI2 expression. High CAI2 expression was an independent prognostic factor in glioma. The absorbance values in the MTT assay after 96 h were .712 ± .031 for the si-control and .465 ± .018 for the si- CAI2-transfected cells, and si-CAI2 inhibited colony formation in U251 cells by approximately 80%. The levels of PI3K, p-AKt, and AKt in si-CAI2-treated cells were decreased. Conclusion: CAI2 may promote glioma growth through the PI3K-AKt signaling pathway. This research provided a novel potential diagnostic marker for human glioma.
Keywords: CAI2